THE EXISTENCE OF INTERNATIONAL COMMERCIAL TERMINOLOGIES 2010 (INCOTERMS 2010) RELATED TO RISK LIABILITY FOR INTERNATIONAL TRADING - Glery Devana, Gede Bendesa Mas; Eka Wisanjaya, I Gede Pasek (Kertha Negara : Journal Ilmu Hukum, 2013)
International trading is an activity undertaken by almost all people in the world. Just like human being, there is no one country that can fulfill the needs of its own life. International based sale and purchase will certainly using the transport services of the goods until it delivered to the buyer. There must be a setting of rule in appointing the parties responsible for the specific risks that arise in the delivery of the goods. Arrangements regarding the risk liability in international trading contained in International Commercial Terminologies 2010 (Incoterms 2010).
Keywords: International Trading, Risk Liability, Incoterms 2010